Intelligent Motion-Controlled Quadruped Robot Using Arduino Systems - Jumaah , Amjed; Qasim , Aseel (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2025)
This work presents RobotSpot, a novel low-cost quadruped robot designed to address the growing need for accessible and robust platforms in robotics education and research Background. The main aims are to develop a system that combines intelligent control with economic feasibility, emphasizing ease of reproduction and modification. The methods involve integrating hybrid control algorithms and conducting experimental evaluations to assess stability and energy efficiency. The results demonstrate reliable operation with an average stability of 88.1% and energy efficiency of 77.5%, highlighting RobotSpot’s potential as a practical and affordable tool for hands-on learning and innovation, especially in resource-constrained academic environments.